ВПЛИВ БАКТЕРІЙ BACILLUS SUBTILIS НА СТАН І АКТИВНІСТЬ ФОТОСИНТЕТИЧНОГО АПАРАТУ РОСЛИН ПШЕНИЦІ ОЗИМОЇ (TRITICUM AESTIVUM L.) - Гончар, А. М.; Патика, М. В. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2022)
Objective. To assess the performance of individual strains of Bacillus subtilis and the efficiency of their action on the condition and activity of the photosynthetic system of juvenile winter wheat plants (Triticum aestivum L.). Methods. Microbiological, instrumental (microscopic), biophysical (determination of photochemical activity of winter wheat sprouts in model conditions of the induction of chlorophyll fluorescence). Results. The technological stability of B. subtilis H38, H40 and H45 strains was shown both during fermentation (formation of viable spore titre in the range of 1.9‒2.4 billion/mL) and during storage of bacterial suspensions (BS) for 60 days (1.8‒2.3 billion spores/mL). Analysis of the influence of B. subtilis H38, H40, H45 on the activity of the photosynthetic system of winter wheat (Triticum aestivum L.) plants revealed a high informative value of induced changes in chlorophyll fluorescence (ICF), which was recorded in the structural organization of chloroplasts of wheat sprouts at the initial, maximum, and stationary levels of fluorescence and viability index (Rfd after 1:50 dilution of BS of B. subtilis strains is 1.56–1.69; Rfd after 1:100 dilution corresponds to the normal quantum efficiency of photosynthesis in the range of 1.20‒1.40). Conclusion. The studied strains of B. subtilis are characterized by high performance (a significant number of spores are formed during the cultivation of bacteria; their number remains relatively stable during a 60-day research period), which implies the possibility of their successful use in production and the possibility of long-term storage of preparations based on them. The prospective use of the evaluated strains for the intensification of the photochemical activity of winter wheat (Triticum aestivum L.) plants in the process of ontogenesis has been proven. This means scientific and practical importance for ecological monitoring, assessment of plant resistance, and the introduction of biological agents in the technology of growing agricultural crops.